Surface modification of aluminium-zinc alloy (AA7075) and its corrosion characteristics / Angel Richard - Angel , Richard (2018)
Aluminium and its alloys are adopted in wide range of applications due to its outstanding advantageous properties such as high electrical and thermal conductivities, good corrosion resistance, highly formable, recyclable and high strength with low density. In the event of corrosive environment, pure aluminium as well as its alloys can be further enhanced through surface modification to improve its corrosive property, inhibit corrosion. In this current research, the focus is on employing novel surface modification with the formation of aluminium oxide nano-porous arrays on aluminium alloy substrate 7075 (AA7075) in order to improve the corrosion properties. Development of the oxide layer was carried out through electrochemical anodization. Subsequently, heat treatment at 450 °C for duration of 1.5 hour with the aim of improving the adhesion strength of aluminium oxide nano-porous arrays and enchance corrosion resistance. Corrosion behaviour of AA7075 is studied with justifications on material properties: adhesion strength, hardness and surface wettability. The adhesion strengths and surface hardness were evaluated by scratch test and Vickers microhardness testing machine respectively. Optical wettability was conducted to inspect surface wettability of AA7075 with utilization of video-based optical contact angle measuring system. Surface topography of the aluminium oxide nano-porous coating formed after anodization as well as heat-treated were investigated by Field Emission Scanning Electron Microscopy (FESEM) while Energy Dispersive X-ray Spectroscopy (EDS) and X-ray diffractometry (XRD) are used for examination of chemical compositions presence in the thin films developed. Heat treated sample has the best adhesion strength of aluminium oxide nano-porous layer and iv the highest hardness compared to substrate and heat treated samples. Corrosion test carried out reveals that anodization ables to improve corrosion resistance of AA7075. Heat-treated AA7075 also enhanced the material properties and increase corrosion protection of with the lowest corrosion rate of 1.29×10-6.